2017
DOI: 10.1016/j.alcohol.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous alcohol use among patients with schizophrenia and depression

Abstract: Given the significant prevalence of hazardous alcohol use in this population, routine screening for hazardous alcohol use and brief interventions could be an effective way of managing this comorbidity. There is a need to develop and evaluate culturally appropriate brief interventions based on patient preference in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
6
18
2
Order By: Relevance
“…Additionally, individuals with a history of smoking were found to be more likely to report hazardous alcohol use. This finding is consistent with previous research indicating the frequent co-occurrence of smoking and excess alcohol use [23, 33, 34]. One study suggests that people who consider themselves to be risk takers were more likely to share a genetic risk with schizophrenia and be smokers [35].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, individuals with a history of smoking were found to be more likely to report hazardous alcohol use. This finding is consistent with previous research indicating the frequent co-occurrence of smoking and excess alcohol use [23, 33, 34]. One study suggests that people who consider themselves to be risk takers were more likely to share a genetic risk with schizophrenia and be smokers [35].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of hazardous alcohol use amongst patients with FEP reported in the current study can be compared to a similar study which examined hazardous alcohol use amongst psychiatric outpatients in Singapore (albeit with a sample population with a diagnosis of schizophrenia or depression) [23]. The prevalence of hazardous alcohol use in the current study among outpatients with FEP was found to be almost double (12.9%) compared to patients with schizophrenia (6.4%).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Educational status was strongly associated with alcohol abuse where those with lower education were more likely to be Epidemiology and Psychiatric Sciences 5 associated with alcohol abuse. This association has been found in previous studies in the local population (Subramaniam et al, 2012c;2017b) as well as in other countries (Andrade et al, 2002;Park et al, 2008). It has been suggested that better-educated people are less likely to engage in risky behaviors, such as smoking and drinking, and are more likely to have healthy behaviors related to diet and exercise.…”
Section: Discussionsupporting
confidence: 79%
“… 5 The prevalence of alcohol use disorder (AUD) is higher among those with severe mental disorders as compared with the general population. 6–8 Different studies conducted in developing countries report that the co-morbidity rate of AUD in affective disorders and schizophrenia ranged from 11.3% to 56% 5 , 6 , 9 , 10 and 9.7% to 74% 5 , 6 , 11 respectively. The large variation in outcomes of such prevalence studies was attributed by the differences in study settings, study design, and AUD screening tool.…”
Section: Introductionmentioning
confidence: 99%